Isolation and Antimicrobial Activity of Fructophilic Lactic Acid Bacteria from Flowers in the University of the Philippines Diliman, Quezon City - Penuliar, Gil M.; Artezuela, Renz Joseph R. (Science Diliman: A Journal of Pure and Applied Sciences, 2022)
Fructophilic lactic acid bacteria (FLAB) is a recently discovered group of lactic acid bacteria that prefers fructose as carbohydrate source. The isolation of FLAB from fructose-rich niches like flowers, in particular, and the gut of insect pollinators suggests that it may be used as probiotics. The objective of this study was to determine if FLAB can be isolated from flowers at the Institute of Biology, University of the Philippines Diliman, and to screen them for antimicrobial activity against bacteria that are commonly associated with intestinal diseases. A total of 20 different isolates were obtained from 14 species of flowers. All isolates were identified as LAB, but only 17 out of 18 isolates were osmotolerant in 30% fructose, and only 8 out of 15 isolates had higher absorbance in Fructose Yeast Peptone Broth, which are characteristics of presumptive FLAB. Seven isolates exhibited inhibitory activity in at least three test bacteria in the primary screening and only four isolates had inhibitory activity in at least two test bacteria, particularly against Enterococcus faecalis and Campylobacter jejuni, in the secondary screening. DNA sequencing and phylogenetic analysis identified isolates MFPS 4.1 and MFRU 7.2 as Weissella spp. The in vitro antimicrobial activities of these isolates can be studied further for possible applications in food and medicine, and their low sequence similarities suggest that the isolates might be novel Weissella species.
Keywords: FLAB, antimicrobial activity, Weissella spp.